Ayurvedic Management of Kitibha Kushta (AYUSHDHARA, 2024)
Psoriasis is long lasting, non-contagious autoimmune disease. Characterized by scaly patches on skin with dry and reddish discoloration. In India incidence rate of psoriasis about 2% to 4%, steroids and immunosuppressive drugs are the treatment option in contemporary science. Due to their limitation and high chance of recurrence. Present case report, A 50 years old female patient presented with a 1 month history of itching and whitish scaly patches on the skin diagnosed as Kitibha kushta (psoriasis). The patient was treated with 15 day course of Shamanaushadi, including Tab. Gandakarasayana, Arogyavardini vati, Cap. Guggulu tiktaka ghrita, and Bactimo ointment. Significant improvement was observed within 15 days, with no signs of recurrence. The treatment protocol adopted based on the Ayurvedic principles, targeting the Vatakapha dosha predominance in Kitibhakushta. This case report highlights the effectiveness of Shamanaushadi in managing psoriasis and support further research to explore its potential as a complementary therapy.